A frequency domain phase/modulation technique for intracellular multicomponent fluorescence analysis: Technical approach and pharmacological applications. Issue 2 (2003) - Praus Praus, P. P.; Sureau Sureau, F. F.; Kocisova Kocisova, E. E.; Rosenberg Rosenberg, I. I.; Stepanek Stepanek, J. J.; Turpin Turpin, P. Y. P. Y.
Abstract : A UV confocal laser microspectrofluorimeter prototype has been adapted for fluorescence lifetime measurements by using a frequency-domain phase/modulation method (modulation frequency 1 to 200 MHz, lifetime resolution: tenth of a ns). This technique enables excited state lifetimes of several fluorescent components to be resolved and determined. Through a global analysis, specific spectral contribution of each species can be monitored with no need to use model spectra. This approach is efficient to distinguish strongly overlapping components (e.g., intracellular multicomponent fluorescence signal) which otherwise cannot easily be discriminated from each other. Experimental set‒up is first described. Application dealing with an antisense oligonucleotide (a synthetic dT15 oligomer analogue containing isopolar, non-isosteric, phosphonate [3'-O-P-CH2 -O-5'] internucleotide linkages) bound to a fluorescent label (tetramethylrhodamine dye), in various solutions and interacting with living cells, is then presented. This is of a major interest for antisense and/or antigene strategies which have recently been developed as efficient ways to cure viral and/or malignant diseases. The frequency-domain phase/modulation technique enabled oligonucleotide stability inside the cells to be checked.